Catecholamine levels with use of electronic and combustible cigarettes - Poudel, Remy; Li, Shen; Hoong, Haoyun; Zhao, Juan; Srivastava, Shweta; Robertson, Rose Marie; Hall, Jennifer L.; Srivastava, Sanjay; Hamburg, Naomi M.; Bhatnagar, Aruni; Keith, Rachel J. (Tobacco induced diseases, 2024)
Smoking elevates catecholamines that increase the risk for cardiovascular disease. Sparse evidence exists about the effects of e-cigarettes and catecholamines. Higher levels of catecholamines could trigger the increased heart rate, blood pressure, and decreased vascular function reported with the use of e-cigarettes. We investigated the difference in urinary catecholamines and their metabolites before and after the use of an e-cigarette containing nicotine or cigarettes compared to no tobacco use. In our observational cohort exposure study, healthy adults aged 21-45 years who were currently using e-cigarettes, cigarettes, or had never used tobacco, participated in an acute exposure visit using their most common tobacco product. Urine was collected before, 1, and 2 hours after a 3-second puff every 30 seconds for 10 minutes on an e-cigarette or straw or use of 1 cigarette. Urinary catecholamines and their metabolites were measured by ultra-high-performance liquid chromatography. Participants (n=323) were grouped by the product used at the visit. We compared levels of creatinine normalized log-transformed urinary catecholamines and their metabolites across groups using Dunn's test following a Kruskal-Wallis test in unadjusted and demographically adjusted models. Prior to use, individuals who used cigarettes (n=70) had lower urinary metabolites from epinephrine, serotonin, and norepinephrine. No differences were seen in those who used e-cigarettes (n=171) and those who did not use tobacco (n=82). In fully adjusted models, 1 h after the use of a combustible or e-cigarette, log-transformed urinary metabolites from norepinephrine (β=1.22; 95% CI: 0.39-2.05, p=0.004 and β=1.06; 95% CI: 0.39-1.74, p=0.002), dopamine (β=0.37; 95% CI: 0.24-0.5, p<0.001 and β=0.15; 95% CI: 0.05-0.26, p<0.001), and epinephrine (β=1.89; 95% CI: 0.51-3.27, p=0.008 and β=1.49; 95% CI: 0.38-2.61, p=0.009) were elevated. In fully adjusted models, combustible cigarette use was associated with elevated urinary norepinephrine (β=0.46; 95% CI: 0.13-0.81, p=0.007) and dopamine (β=0.19; 95% CI: 0.06-0.31, p=0.003) 1 h after use. We found that the use of both e-cigarettes and cigarettes was associated with elevated urinary catecholamines or their metabolites. Catecholamines could be useful as a biomarker of harm for tobacco use and considered by tobacco regulatory scientists in future research.